Nuno Freire de Andrade, Grand-Master of Christ. Andrade’s tradition and relations with de Portuguese kingdom - Pichel Gotérrez, Ricardo (Madrygal. Revista de Estudios Gallegos, 2014)
In this article we offer a historiographical approach to the Casa de Andrade, one of the most important noble families in medieval Galiza, and their relations with the Castilian kingdom and especially the Portuguese kingdom throughout the 14th century. Thus, we will focus on the figure of Nuno Freire de Andrade, Grand-Master of the Order of Christ and torchbearer for Kings Pedro I and Fernando I of Portugal.